Street Children and Homeless Youth A Cross-Cultural Perspective - Aptekar, Lewis; Stoecklin, Daniel; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book deals with street children who live in the developing world, and homeless youth who are from the developed world. They are referred to as children in street situations (CSS) to show that the problem is both in the children and in the situation they face. The book examines several aspects of the children and their street situations, including the families of origin and the homes they leave, the children$1 (Bs social life, and mental health. Other aspects are the problems of published demographics, the construction of public opinion about these children and the, often violent, reactions from authorities. The book then discusses current research on children in street situations, as well as programs and policies. The book ends with recommendations about programs, policies and research.s
Chapter 1: Introduction: A New Vision of Street Children and Homeless and Runaway Youth -- Chapter 2: Children in Street Situations: Street Children and Homeless Youth -- Chapter 3: Group Dynamics of Children in Street Situations -- Chapter 4: Research with Children in Street Situations -- Chapter 5: Programs; Typical and Exemplary -- Chapter 6: Summary, Conclusions and Recommendations.
Keywords: Social sciences; Quality of Life; Social work; Quality of Life -- Research; Applied psychology; Developmental psychology; Social Sciences; Quality of Life Research; Child and School Psychology; Social Work; Psychotherapy and Counseling